Factors Influencing Blockchain-based Mobile Banking Adoption: Evidence from a Developing Country - Kabir, Mohammad Rokibul; Khan, Md. Muntasir Hasan; Ibrahim , Md. (Journal of Technology Management and Business, 2022)
This study attempts to explain the factors influencing blockchain-based mobile banking acceptance in Bangladesh. Based on a technology acceptance framework termed UTAUT2 (unified theory of acceptance and use of technology 2), an enhanced model with a mediating variable is built for this research. Data were collected from the first-ever blockchain-based mobile banking stakeholders in Bangladesh called ’UPAY’ by applying a structured questionnaire. Structural equation modeling was then processed using Smart-PLS. There are eight direct hypotheses and one mediating hypothesis in this research. The findings reveal that all of the direct hypotheses except the impact of social influence on the behavioural intention (BI) to use blockchain are statistically significant. The mediating role of BI in the connection between facilitating conditions (FC) and actual blockchain use is also supported. The combination of FC and BI contributes to 88.8% of the variation in blockchain usage behaviour for mobile banking adoption. The findings of this study can help banking regulators devise a strategy for engaging a significant number of banks to create a blockchain-based mobile banking platform Keywords: Blockchain use behaviour; Mobile banking, PLS-SEM; UPAY; UTAUT2